Criminal Implications of Government Policy on Visa-Free Enforcement (Misuse of Residence Permits Based on Tourism) - Arif Rohman (Proceedings of AICS - Social Sciences, 2017)
Government policy to explore the source of state budgeting base on tax impressed is still not enough when compared to policies in the development sector. The potential that can be explored is tourism, considering Indonesia is an archipelago and abundant tourism potential both inland and marine tourism. Tourism potential is expected to increase state revenues and revenues for regions that have tourism. Various ways to accelerate the development of tourism, both physical and human resources are poured form of policy; one of these policies is enforced visa-free for tourists. However, the policy is not in line with the supervision so that it is abused by foreigners. This research use normative method, research that relies on norms and legal principles related to government policy in the application of visa-free for foreigners who impact on crime. The results of this study illustrate that, the government's policy on tourism has a negative impact that is the abuse of residence permit for foreigners. While the positive impact of the regulation is the number of tourists who come to Indonesia that increased, so as to increase revenue for the state and income for the region. However, the most important of these regulations is the absence of prevention efforts.  Tourists should only do tourism activities, but instead even many foreigners who work in the territory of Indonesia with the mode of tourism (visa-free). Tourism management model that must be implemented is the supervision of tourists. So the burden and heavy duty on the Directorate General of Immigration is because the institution is authorized both the enforcement and supervision of foreigners who come to Indonesia.